Distribution and natural enemies of avocado lace bug Pseudacysta perseae (Hemiptera: Tingidae) in Nayarit, Mexico - Cambero-Ayón, Carlos Bryan; Rodríguez-Palomera, Marcia; Robles-Bermúdez, Agustín; Coronado-Blanco, Juana María; Rios-Velasco, Claudio; Cambero-Campos, Octavio Jhonathan (Revista Colombiana de Entomología, 2019)
The aim of this study was to determine the distribution of the lace bug Pseudacysta perseae and to identify their natural enemies in avocado orchards in the state of Nayarit, Mexico; weekly sampling was conducted on 30 commercial orchards with Hass, Hall and Choquette avocado cultivars in the municipalities of Xalisco, Tepic and San Blas, from January to July 2016. The specimens collected were transferred to the Laboratory of Agricultural Parasitology of the Universidad Autónoma de Nayarit - UAN, and subsequently were individually separated to obtain parasitoids, predators and entomopathogenic fungi. Out of a total of 30 sampled areas, only P. perseae was recorded in 20 of the orchards, with an average infestation level of 434 eggs, 107 nymphs and 23 adults per site. A total of 175 natural enemy specimens were identified, of which 61 were parasitoids belonging to Trichogrammatidae family, 58 adults of P. perseae with symptomatology of fungal infection, identified morphological and molecularly as Metarhizium anisopliae and Beauveria bassiana, with incidences of 3.0 % and 9.4 %, respectively. In addition, 56 predators were caught belonging to the species Cycloneda sanguinea, Stethorus sp. and Pentilia sp.